2014
DOI: 10.1371/journal.pone.0092883
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae Persisted in Microcosm for 700 Days Inhibits Motility but Promotes Biofilm Formation in Nutrient-Poor Lake Water Microcosms

Abstract: Toxigenic Vibrio cholerae, ubiquitous in aquatic environments, is responsible for cholera; humans can become infected after consuming food and/or water contaminated with the bacterium. The underlying basis of persistence of V. cholerae in the aquatic environment remains poorly understood despite decades of research. We recently described a “persister” phenotype of V. cholerae that survived in nutrient-poor “filter sterilized” lake water (FSLW) in excess of 700-days. Previous reports suggest that microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…To determine if GASP-700D ( Jubair et al, 2014 ) sustained a mutation in the flrA gene, we PCR amplified the gene from the GASP-700D genome with two convergent PCR primers [aa778 and aa780 (Supplementary Table 1 )] using standard PCR conditions. The amplicon was purified using Qiagen PCR Purification Kit (Qiagen, Valencia, CA, United States) and sequenced with help from the Interdisciplinary Center for Biotechnology Research (ICBR) at University of Florida; sequence analysis revealed that GASP-700D sustained a 49-bp deletion mutation in flrA gene (we hereafter referred this strain as GSΔ flrA ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine if GASP-700D ( Jubair et al, 2014 ) sustained a mutation in the flrA gene, we PCR amplified the gene from the GASP-700D genome with two convergent PCR primers [aa778 and aa780 (Supplementary Table 1 )] using standard PCR conditions. The amplicon was purified using Qiagen PCR Purification Kit (Qiagen, Valencia, CA, United States) and sequenced with help from the Interdisciplinary Center for Biotechnology Research (ICBR) at University of Florida; sequence analysis revealed that GASP-700D sustained a 49-bp deletion mutation in flrA gene (we hereafter referred this strain as GSΔ flrA ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite decades of investigations, the physiological and genetic basis of the persistence of V. cholerae in aquatic reservoirs, particularly during inter-epidemic periods, remains to be fully elucidated. Possible survival mechanisms in nutrient-poor and stressful aquatic reservoirs include: (a) adopting a viable but non-culturable (VBNC) state ( Xu et al, 1982 ; Colwell and Huq, 1994 ), (b) switching from planktonic to biofilm lifestyle ( Wai et al, 1998 ; Yildiz and Schoolnik, 1999 ; Ali et al, 2002 ), and/or (c) assuming “persister” and “growth advantage stationary phase” (“GASP”) phenotypes as described recently ( Jubair et al, 2012 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if VpsA is essential for the expression of rugose colony phenotype in Haitian altered V. cholerae strain, we created a vpsA in-frame deletion mutation in the background of HC16R strain (Table 4), using genetic manipulations described recently [18]. An internal in-frame deletion in the vpsA [HC16RΔ vpsA (Table 4)] was created and the mutation was verified by PCR and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The SCVs are known for their ability to resist antibiotics, remain persistent in mammalian cells and cause latent or recurrent infections in the infected host. Several pathogenic bacteria have been reported to produce SCV including, Burkholderia cepacia [ 2 ], Pseudomonas aeruginosa [ 5 ], Salmonella [ 4 ], Vibrio cholera [ 6 ], Brucella melitensis [ 7 ], Escherichia coli [ 8 ], Serratia marcescens [ 9 ], Staphylococcus aureus [ 10 ], and Staphylococcus epidermidis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%